THE PRESENCE OF ROMAN LEGAL TRADITION IN THE INSTRUMENTS OF DEBT INSURANCE OF THE CRES-OSOR STATUTE - Matić Matešković, Ines (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
The author in the paper analyzes legal institutions aimed at securing creditors’ claims and the position of debtors and creditors in the Cres-Osor Statute in case of the debtor’s failure to fulfill the debt. The statute pays particular attention to the pledge right and, in various ways, regulates rules regarding the establishment of pledges on movable and immovable property, as well as the sale of pledged items and the satisfaction of creditors from their value. The paper provides an overview of the legal regulation of these institutions and their specificities, and based on the analysis conducted, critically evaluates the genesis of these institutions and the influence of Roman legal tradition on the development of securing claims in the Cres-Osor Statute law.